TOWARDS A BETTER UNDERSTANDING OF THE FACTORS OF ENTREPRENEURIAL FAILURE: AN EXPLORATORY STUDY OF ENTREPRENEURS IN THE SFAX REGION OF TUNISIA - Souissi, Mourad (Journal of Business Studies and Management Review, 2025)
Entrepreneurial failure remains a complex, multi-dimensional subject of study that continues to generate academic debate, due to the lack of consensus on its definition and implications. While some researchers associate it with cessation of activity or economic failure, others see it as a learning and resilience process for the entrepreneur. This diversity of interpretations has led to the emergence of different approaches to better understand this phenomenon. This study explores the factors behind entrepreneurial failure in Tunisian SMEs, specifically in the Sfax region. The main objective is to identify the internal and external causes leading to the failure of new SMEs, focusing on the role of the entrepreneur, available resources and the contextual environment. Using an exploratory qualitative approach, 20 entrepreneurs were interviewed to gather data on their experiences, challenges and obstacles encountered. The results reveal that the failure of Tunisian SMEs results from the complex interaction of several factors. The main factors identified include a lack of managerial skills, difficulties in accessing finance, cumbersome administrative bureaucracy, as well as a lack of institutional support. Although entrepreneurial motivation and commitment are important, they are often insufficient in the face of structural and contextual obstacles to SME development. This study sheds light on the limitations of public support policies and suggests ways of improving the sustainability of Tunisian SMEs.